APPENDICITIS - CLASSIFICATION, REASON (Proceedings of International Educators Conference, 2024)
Appendicitis is the most common surgical disease of the gastrointestinal system and one of the most dangerous diseases. The danger of the disease is, first of all, the inevitability of its rapid development and appearance of serious life-threatening complications. It is very likely that a person will encounter acute appendicitis during his life. 5-10% of people are diagnosed with this disease.Appendicitis can develop in people of any age and gender. However, statistics show that most often this inflammation is observed in people aged 5-40. Among patients aged 20-40, the number of female patients is twice as large as that of men, but among patients under 20 years of age, men predominate. In general, women are more affected than men. After the age of 40, the probability of developing the disease decreases significantly, but is not equal to zero. Therefore, appendicitis develops even in older people. In addition, appendicitis is occasionally diagnosed in children under 5 years of age.